Yield components and reproductive, physiological, and root traits used in early selection for nitrogen use efficiency in corn - Morais, Pedro Patric Pinho; Sousa, Massaine Bandeira e; Galli, Giovanni; Andrade, Luciano Rogério Braatz e; Fritsche-Neto, Roberto; Oliveira, Aluízio Borém de (Pesquisa Agropecuaria Brasileira, 2018)
The objective of this work was to examine the possibility of using yield components and reproductive, physiological, and root traits in early selection for nitrogen use efficiency (NUE) in corn. Sixty-four inbred lines were evaluated under two nitrogen fertilization levels: ideal and low. The evaluations were performed at three phenological stages: eight fully-expanded leaves, tasseling stage, and physiological maturity. It is possible to select superior lines for NUE, but the yield components did not show differential behavior under the different nitrogen levels evaluated. Root, reproductive, and physiological traits are not promising for early selection of corn lines with high NUE. Likewise, the eight-leaves and tasseling stages were not promising for this purpose, since NUE should be estimated taking grain yield into account. However, indirect selection for NUE can be performed via number of ears or using the selection index considering number and weight of ears.